2014
DOI: 10.3400/avd.ra.14-00037
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Bridge as a Structure of “Double-Edged Sword” for the Coronary Artery

Abstract: Myocardial bridge (MB) is a chance anatomical structure, comprised of the myocardial tissue, with which the coronary artery running in epicardial adipose tissue is partly covered. It is predominantly present in the left anterior descending artery (LAD) and recognizable through imaging techniques as changes in blood fl ow within the LAD that arises from MB contraction at cardiac systole. Such changes in blood fl ow infl uence the pathophysiology of coronary circulation and atherosclerosis development, thus gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Myocardial bridging is defined as a segment of a major coronary artery course through the myocardium that normally has an epicardial course [15,16]. In the last decade, it was shown that myocardial bridging can be very well depicted by CCTA which has increased the interest in this anomaly [3,17].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial bridging is defined as a segment of a major coronary artery course through the myocardium that normally has an epicardial course [15,16]. In the last decade, it was shown that myocardial bridging can be very well depicted by CCTA which has increased the interest in this anomaly [3,17].…”
Section: Discussionmentioning
confidence: 99%
“…The vessel is running intramurally and thus is being bridged by muscle fibers. Myocardial bridging predominantly involves the LAD [1]. A superficial and a deep type of MB may be distinguished.…”
Section: Characteristics Of Myocardial Bridgesmentioning
confidence: 98%
“…High shear stress leads to alignment of endothelial cells in the direction of blood flow, therefore being more resilient to the diffusion of pro-atherogenic factors. Atherosclerosis is induced in the segments proximal to an MB however, caused by turbulent and complex blood flow due to systolic flow reversal and increased intra luminal pressure in the proximal segment [1].…”
Section: Characteristics Of Myocardial Bridgesmentioning
confidence: 99%
“…We calculated the MMI as MB length (mm)×MB coverage; 1, 2 or 3. 3 The presence or absence of atherosclerotic plaque proximal to the MB was assessed. When present, plaques were categorized into 5 groups (no plaque, non-calcified, mixed, calcified, and stented).…”
Section: Discussionmentioning
confidence: 99%